Design of a Dual-Band Bidirectional Antenna Using Superellipse-Monopole-Fed Rectangular Ring for IEEE 802.11 a/b/g/n Applications - Ekajit Khoomwong; Chuwong Phongcharoenpanich (International Journal of Antennas and Propagation)
This paper presents the design of a dual-band bidirectional ring antenna fed by a superellipse surface probe for 2.4/5 GHz WLAN applications. The Method of Moments (MoM) with RWG basis function was utilized in the study and design processes. A prototype antenna was fabricated successfully with the advantages of simple and low-cost structure. The measured impedance bandwidth of 810 MHz (2.10–2.91 GHz) and 2.39 GHz (3.57–5.96 GHz) is achieved for the first and second band, respectively. The peak gains are also feasible, 4.67 dBi at 2.45 GHz and 7.83 dBi at 5.5 GHz, with bidirectional radiation patterns for both bands. From the experimental field tests, the proposed antenna was suitable for most applications in long and narrow communication sites in 2.4/5 GHz bands as desired. Also, the measured and calculated results were in good agreement.